The Suppression of Irrelevant Semantic Representations in Parkinson’s Disease - Isaacs, Megan L.; McMahon, Katie L.; Angwin, Anthony J.; Copland, David A. (Frontiers in Human Neuroscience, 2019)
The impairment of lexical-semantic inhibition mechanisms in Parkinson’s disease (PD) remains a source of contention. In order to observe whether people with PD are able to suppress irrelevant semantic information during picture naming, the present study employed an object-based negative priming paradigm with 16 participants with PD and 13 healthy controls. The task required participants to name a red target image while ignoring a superimposed, green distractor image. The semantic relationship between the distractor image and the target image of the subsequent trial was manipulated, such that the distractor image was identical, semantically related, or semantically unrelated to said target image. The PD group and the control group were slower in naming a target image that had previously served as a distractor image, relative to naming a target image that was unrelated to the previous distractor image. Thus, a negative priming effect was present in both groups. Furthermore, no significant difference in the magnitude of this effect was observed between the control and PD groups. When considered in the context of existing literature surrounding negative priming in PD, these results suggest that inhibition is subserved by multiple, domain-specific mechanisms and that the inhibitory processing of visual-semantic stimuli is intact in PD.